Research portfolio - Amweenye, Fares Frans (Rhodes University, Faculty of Education, Department of Education, 2004)
What is the portfolio and what are its purposes? I must define the portfolio as a summative document bearing the valuable experiences learned in a particular course of study. In this context, portfolio can be viewed as a selective entity that represents the level of learning, in terms of academic/professional growth and development, attained in one's participation in a particular course of study such as this Master one I have been attending. Portfolio can be educationally utilized to reflect and evaluate one's learning. As one goes throughout paging, one locates the level of learning achieved in terms of anticipated knowledge, understanding, and experiences, skills and attitudes or overly learning competencies. The level of development one has gone through in attempts to respond to the expected learning outcomes surface out more easily. And if further learning be conducted, the portfolio must as well shows the ways ahead. With these few words, I have attempted to present the portfolio as a useful tool that represents the level of advancement attained in learning. This portfolio comprises of my educational partaking in Rhodes University's master program (theory and practice, in particular what and how I have gained from that program participation. It may also present what I cold not learn. The arrangement of the portfolio contents assumes a progressive procession, being structured in terms of the assignments taken. There are five pieces of assignments in this research portfolio. The first assignment is a contextual analysis of the Education Theory and Practice (ETP) curriculum of our current teacher education program, namely Basic Education Teachers' Diploma. It looks at the theoretical framework that informs and shapes everyday teaching and learning practices, particularly the degree to which we have been able to implement the theoretical perspectives into operational practices. To this is how our college is equipped with the technologies necessary for possible practices of the curriculum. The other emphasis focuses at the historical backgrounds that necessitated the undertaking of the BETD as an instrument of reforming and transforming the basic education rightly at the independence. The other area is on the question of how the curriculum or program intakers, the entering students, have been prepared to consume the curriculum program. Since the program has been as well designed to address and meet the four major national goals of education for all, another part has been focused on these goals so far as to locate the degree of attainment. The second assignment is about contrasting and comparing the two main held dominant worldwide views of knowledge- namely behaviorism and constructivism. Each branch of knowledge is looked at firstly with particular attentions paid to its own individual versions of knowledge and its development and acquisition. The other focuses examine which base seems to offer better explanations of what knowledge is and how it can best be constructed and acquired in any educational setting. The third assignment is that of literature review. I have chosen action as an area that I would be interested in exploring much further. Action research is what eventually became a part of my research proposal in which I would research on how our college students carry out their action research projects to examine their own classroom makings. It has been therefore important to read what others have written about this field and locate the lessons that can be illuminated on our own curriculum context. The literature review paves the way to the research proposal. The research proposal or a research plan as I would often call it, sets the context, purpose, theoretical position and information gathering methods under which the research process will take place. The research proposal has thus been the navigating compass despite the that realities as the practical journey itself took off some deviation unavoidably came in as necessitated by the underlying research process itself. The research proposal finally accumulates into the sought, the final assignment. A critical view illustrates that this piece is actually another contextual inquiry like the first work only that this is viewing our supposed curriculum outcomes: our students, our products and how they have been equipped to carry out the research. Their research, with its successes and shortcomings, I have concluded, firmly serves to reflect the kind of education delivered from our teacher colleges. The portfolio contents also demonstrate the course orientation: focusing on one's professional field. At end, I see this research portfolio as myself, a mirror that reflects my academic and professional participation in Rhodes University's world and its vision and mission expresses in the theme of where leaders learn. It thus represents the personal, academic and development accomplished throughout this Masters' course. In the other way around, I see it as reflecting what Rhodes can offer as from when the prestigious Augustana College, my American institution, has prepared after its boundaries.
Keywords: Education -- Namibia; Educational change -- Namibia; College teachers -- Training of -- Namibia; Curriculum planning -- Namibia; Teaching -- Namibia; Universities and colleges -- Curricula